2011
DOI: 10.1073/pnas.1109769108
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of human signal regulatory protein alpha in Rag2−/−γc−/−mice improves engraftment of human hematopoietic cells in humanized mice

Abstract: Transplantation of human hematopoietic stem cells into severely immunocompromised newborn mice allows the development of a human hematopoietic and immune system in vivo. NOD/scid/γ c −/− (NSG) and BALB/c Rag2 −/− γ c −/− mice are the most commonly used mouse strains for this purpose and a number of studies have demonstrated the high value of these model systems in areas spanning from basic to translational research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(183 citation statements)
references
References 47 publications
5
178
0
Order By: Relevance
“…In fact, the capacity of the ectopic marrow to attract and retain rare circulating HSCs advocates its function as a "stem cell trap," ultimately providing a tool to investigate the physiological factors and mechanisms underlying the still debated concept of the HSC niche. Furthermore, on the basis of the concept of mutual influences between the BM microenvironment and leukemia cells (27,28), the possibility of establishing a human origin BM microenvironment in humanized hematopoietic murine models (29)(30)(31) has a large relevance to investigate the development and progression of blood cell malignancies. Last but not least, the generation of an extramedullary bone organ, accessible to advanced imaging techniques (e.g., intravital confocal microscopy) (14), opens the perspective to investigate and exploit processes underlying the efficient expansion of HSCs for therapeutic purposes (13).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the capacity of the ectopic marrow to attract and retain rare circulating HSCs advocates its function as a "stem cell trap," ultimately providing a tool to investigate the physiological factors and mechanisms underlying the still debated concept of the HSC niche. Furthermore, on the basis of the concept of mutual influences between the BM microenvironment and leukemia cells (27,28), the possibility of establishing a human origin BM microenvironment in humanized hematopoietic murine models (29)(30)(31) has a large relevance to investigate the development and progression of blood cell malignancies. Last but not least, the generation of an extramedullary bone organ, accessible to advanced imaging techniques (e.g., intravital confocal microscopy) (14), opens the perspective to investigate and exploit processes underlying the efficient expansion of HSCs for therapeutic purposes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Continued genetic modifications of candidate host mice will probably enable at least some of the species-specific needs to be addressed in the future. These include the possibility of creating transgenic mice that will express species-specific human cytokines, or the use of humanized mice (mice transplanted with human haematopoietic or local tissue components) to create more human-type microenvironments -as has proved useful for certain types of normal human cells [53][54][55][56][57] . Orthotopic injections of CSCs into various target organs may also prove useful, and mimicry of natural tumour immunosurveillance mechanisms may be achievable using injections of specific immune effector cells (TABLE 2).…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…24 This in vitro finding is also applicable to the in vivo setting, as shown by another study in which a human SIRPA BAC transgene introduced into Rag2 null Il2rg null mice on a mixed 129; BALB/c background significantly improved the efficiency of human hematopoietic engraftment. 29 SIRPA is a transmembrane protein that contains 3 Ig-like domains within the extracellular region. It is expressed in macrophages, myeloid cells, and neurons, and interacts with its ligand CD47 through its respective IgV-like domains, where the NOD strain has specific polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…44 Furthermore, a recent study has shown that the enforced expression of human SIRPA by a human BAC transgene enables the 129;Balb/c.Rag1 null Il2rg null mouse to engraft human cells as efficiently as the NSG mouse. 29 Therefore, in xenograft models, the degree of SIRPA-CD47 interaction decided by Sirpa polymorphism is one of the most critical factors to achieve efficient human cell engraftment. Further study is required to understand how the different binding affinity between these mouse polymorphic SIRPAs and human CD47 is translated into cytoplasmic signaling that leads to respective efficiency for xenotransplantation capabilities.…”
mentioning
confidence: 99%